Rare species advantage? Richness of damage types due to natural enemies increases with species abundance in a wet tropical forest. (7th June 2013) - Bachelot, Bénédicte; Kobe, Richard K.; Vesk, Peter
Summary 1 The Janzen–Connell hypothesis (JC) is one potential mechanism to explain the maintenance of high alpha diversity of tree species in tropical forests, operating through differential pressure by natural enemies. 2 We proposed that this differing pressure could arise from the richness of damage types due to natural enemies (RDNE). Following a community compensatory trend (CCT), we hypothesized greater RDNE on common species than on rare species. 3 We evaluated this novel interpretation of the JC by assessing damage patterns on leaves, as a proxy for natural enemy species in 44 tree species. We first evaluated which abiotic and biotic factors affect RDNE. Then, we tested whether increasing RDNE leads to an increasing amount of foliar damage. 4 We found that RDNE Was affected by biotic environments: RDNE increased with mean seedling species abundance. RDNE was higher on species occurring near more closely related neighbours. Was not impacted by abiotic factors. Yet, seedlings of shade‐tolerant species hosted a higher RDNE than seedlings of shade‐intolerant species. Was positively correlated with amount of foliar damage at the species level. 5 Finally, we tested whether RDNE increased seedling mortality risk. We found that Foliar damage, species abundance and RDNE2 increased mortality risk. Richness of damage types due to natural enemies linearly decreased mortality risk more strongly than RDNE2 increased it. Seedling age decreased mortality risk. 6 Synthesis. The richness of damage types due to natural enemies increased with abundance of the host species, suggesting an important role of enemy diversity in the maintenance of tree diversity. Supporting a novel interpretation of the Janzen–Connell hypothesis, we found a greater mortality risk with increasing RDNE2, but not with increasing RDNE. There was a stronger negative linear effect of RDNE on mortality risk. Rare species with low RDNE as well as species with very high RDNE suffered greater mortality than species hosting intermediate RDNE, reinforcing the complexity of the effect of multiple enemies on prey.